A Study of the Weakness of Honesty (Lying) in the Teachings of the Qur'an - Sayyid Ali Naqi Ayazi (آموزه‌های قرآنی, 2022)
Social capital in any system is based on trust and honesty and the amount of social capital will increase as much as this trust increases. But if mutual trust is undermined and people do not trust each other, this will be opposed to social capital. The Qur'an, as a written culture of the Muslim community, can provide a way to identify the factors, effects and consequences that have caused this failure. The main question of the research is about the quiddity of social factors, interactions and effects of weakness of honesty [lie] in the teachings of the Qur'an that in order to achieve the goal, identify the factors affecting the weakness of honesty and analysis of its roots, achieving the grounds and conditions for occurrence of untruth and recognizing its consequences and effects, the method of inductive qualitative content analysis has been done. Six factors of lying are obtained among the teachings of the Qur'an in this study, which are carried out by deceptive interactions of speech justifiers, persuasive literature, and the expression and provocation (agitation, incitement) of false feelings and it has psychological projection, vulnerable consequences, with repeated lie and scandals.